Leonardo da Vinci's studies of the brain. Issue 10179 (6th April 2019) - Pevsner, Jonathan
Summary: Leonardo da Vinci (1452–1519) contributed to the study of the nervous system. His earliest surviving anatomical drawings (circa 1485–93) included studies of the skull, brain, and cerebral ventricles. These works reflected his efforts to understand medieval psychology, including the localisation of sensory and motor functions to the brain. He was also the first to pith a frog, concluding that piercing the spinal medulla causes immediate death. After a 10-year interval in the early 1500s Leonardo resumed his anatomical studies and developed a method to inject hot wax into the ventricular system, creating a cast that showed the shape and extent of the ventricles. During this period he also progressed in his understanding of the anatomy of the cranial nerves. Besides being the first to identify the olfactory nerve as a cranial nerve, his dissections showed him that contrary to previous theories, the nerves do not converge on the lateral or third ventricles. Leonardo also performed detailed studies of the peripheral nervous system. Although his discoveries had little influence on the development of the field of anatomy, they represent an astonishingly sharp break from the field that had seen little if any progress in the previous 13 centuries. His work reflects the emergence of the modern scientific era and forms a key part of his integrative approach to art and science.